Embedded Digital MIMO Radar Using SDR for Target Detection and RCS Measurement. Issue 1 (2nd January 2016) - Shome, Subhankar; Bera, Rabindranath; Maji, Bonsibadan; Sur, Samarendra Nath; Bera, Soumyasree
ABSTRACT: Multiple input multiple output (MIMO) radar has superior performance to conventional one. It has been introduced in almost every field of conventional radar now days. The MIMO techniques have been well studied where they offer benefits in multipath fading environments. Inspired by these, MIMO are applied to radar and offer advantages such as improved resolution and sensitivity. But these systems consist of large antenna, a lot of electronic equipment and powerful computational unit. In these applications, small size embedded software define radio (SDR) can be used. Then real time processing of a radar signal can also be much simpler. For above-mentioned applications, it is possible and reasonable to have small devices with low power consumption that perform real time correlation-based processing. Moreover, dimensions of the processor boards are very compact and they can be easily integrated into small cases. That is why it is good to transfer radar signal processing algorithms to the embedded system. The recent development of digital MIMO radar is now module in these SDR systems. Our motivation is to design a spread spectrum-based digital MIMO SDR radar which is small in size and may be a low-cost solution where we can bypass all the huge instrumentation complexity.